2018
DOI: 10.1016/j.jsams.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Does player time-in-game affect tackle technique in elite level rugby union?

Abstract: It appears that player time-in-game does not affect tackler or ball carrier tackle technique proficiency at the elite level. More tackles occurring in the final quarter of a game provides an alternative explanation to more tackle-related injuries occurring at this stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…3 Tackling is regarded as the most common cause of injury and concussion in rugby union. 4,5 Correct technique in the tackle is essential for safe and successful tackle outcomes, [6][7][8] whilst poor tackle technique is a reported risk factor for injury 9,10 and direct head impact causation. 2,11 This indicates the importance for concussion injury prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…3 Tackling is regarded as the most common cause of injury and concussion in rugby union. 4,5 Correct technique in the tackle is essential for safe and successful tackle outcomes, [6][7][8] whilst poor tackle technique is a reported risk factor for injury 9,10 and direct head impact causation. 2,11 This indicates the importance for concussion injury prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In one season alone, one study found that 23% of elite level Rugby Union participants suffered a concussion (Shuttleworth-Edwards et al, 2008). It is well understood that both correct tackler and ball carrier technique are necessary for successful and safe participation in rugby union (Hendricks & Lambert, 2010Tierney, Denvir, Farrell, & Simms, 2018a, 2018cTierney, Krosshaug, Wilson, & Simms, 2015), and that incorrect tackle technique is a risk factor for injury Hendricks et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However there is no specific evidence in regards to the length of time it takes for technique to move from deviation to deterioration. In contrast to this, a study on player time on rugby performance found no significant effect of fatigue on technique (Tierney, Denvir, Farrell & Simms, 2016). This study did not specifically look at deviation in technique just deterioration.…”
Section: Fatiguementioning
confidence: 65%